The multiple semantics of PIE deictic *bhe in Baltic - de Vaan, Michiel (Baltistica, 2018)
The traditional equation of Lithuanian connective bè, be- with the preposition bè ‘without’ can be supported by a more detailed reconstruction of the semantic history of the words. This analysis can be supported by outer-Baltic evidence for the PIE deictic elements *bhe, *bho.